Digital media contracts - Williams, Alan P. (Oxford University Press, 2011)
Digital Media Contracts contains a collection of sample agreements, presenting annotated contracts from the digital media industry in typical formats for the industry. Included are agreements for digital downloads, user generated content, social networks, wireless apps and cloud computing. It goes beyond traditional precedents by giving practical, commercially-grounded commentary and background information to assist both readers intending to draft their own documents and those looking for hands-on guidance when reviewing standard form documents received from other parties. Lawyers working in the digital media industry, private practitioners and in-house lawyers will find this work especially useful. Its jurisdictional scope is primarily focused on the UK with comparative comments on similar agreements in the US, with input from lawyers based in the US. This comprehensive guide will provide practical support in the form of checklists and flow-charts, and will include additional supporting documents such as standard NDAs and sample Heads of Agreement.